Up gradation of Network monitoring Software with Absolute Zero Downtime and no Performance Loss Using Double virtualization (International Journal of Scientific Research and Management (IJSRM), 2015)
This paper explains about the network monitoring software provided by different networking company .In general all of the NMS of different networking company have a general deployment architecture .and these NMS are regularly upgraded to the updated technology .but the procedure of up gradation followed by them in current market as many disadvantages which is discussed in this paper and a new procedure of up gradation is explained which will overcome the disadvantages of the existing procedure.